DESAIN PROTOTIPE PENJARA PEREMPUAN DENGAN PENDEKATAN RETHINKING TYPOLOGY DAN ARSITEKTUR EMPATI - Michael Michael; Priscilla Epifania Ariaji (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2023)
Women Prison Architecture is the design and structure of a prison building specifically intended to hold female prisoners. Women's prisons are designed with the special needs, security and welfare of female prisoners in mind. Women's prisons in Indonesia have various problems, especially the physical environment that has not followed the standards so that the conditions of this prison become less humane for women prisoners. This phenomenon of problems occurs due to a lack of empathy and understanding of the definition of punishment towards the needs of women in Indonesia. Empathy is an integral part of architecture, because without empathy in the design process it can lead to architectural design failures that can reduce the quality of life of building users. This paper discusses the design of a prototype women's prison with a rethinking typology and empathy architecture approach. The first step of Rethinking Typology of women's prisons by dissecting each element of the typology of women's prisons based on the needs of women prisoners and the next step is completed through; programming; configuration of a new typology of women's prison architecture. The purpose of this Rethinking Typology is to produce a prototype of a women's prison that meets the standards and needs of women today. The new prototype emphasizes humanitarian standards and the needs of women. The new prototype is designed to respond to nature in order to create a healthy atmosphere for women prisoners. The surveillance system utilizes anti-authoritarian principles through the use of technology to create a non-intimidating prison environment. The design is also supported by re-empowering architectural programming so that women prisoners can be productive while in prison. This prototype can provide a balance of conducive living spaces that can help encourage women prisoners in the recovery or rehabilitation process for reintegration into the community. Keywords: empathic architecture; prison prototype; rethinking typology; women prison architecture; women prisoners Abstrak Arsitekur Penjara Perempuan merupakan sebuah desain dan struktur bangunan penjara yang ditujukan khusus untuk menahan tahanan perempuan. Penjara perempuan dirancang dengan mempertimbangkan kebutuhan, keamanan, dan kesejahteraan khusus dari narapidana perempuan. Penjara perempuan di Indonesia memiliki berbagai permasalahan terutama permasalahan lingkungan fisik yang sudah tidak mengikuti standar sehingga kondisi penjara ini menjadi kurang manusiawi terhadap narapidana perempuan. Fenomena permasalahan ini terjadi dikarenakan oleh kurangnya empati dan pemahaman mengenai definisi hukuman terhadap kebutuhan perempuan di Indonesia. Empati merupakan sebuah bagian yang tidak terpisahkan dari arsitektur, karena tanpa adanya empati dalam proses perancangan dapat mengakibatkan kegagalan desain arsitektur yang dapat menurunkan kualitas kehidupan pengguna bangunannya. Tulisan ini membahas tentang desain prototipe penjara perempuan dengan pendekatan rethinking typology dan arsitektur empati. Langkah pertama dari Rethinking Typology penjara perempuan dengan cara membedah setiap elemen tipologi penjara perempuan berdasarkan kebutuhan narapidana perempuan dan langkah selanjutnya penyelesaian melalui; penyusunan program; konfigurasi tipologi arsitektur penjara perempuan baru. Tujuan dari Rethinking Typology ini untuk menghasilkan sebuah prototipe penjara perempuan yang memenuhi standar dan kebutuhan perempuan masa kini. Prototipe baru ini menekankan pada standar kemanusiaan dan kebutuhan perempuan. Prorotipe baru ini didesain agar merespon alam agar dapat menciptakan atmosfer yang sehat bagi narapidana perempuan. Sistem pengawasan yang digunakan dengan prinsip anti-otoriter melalui penggunaan teknologi sehingga dapat menciptakan suatu lingkungan penjara yang tidak mengintimidasi. Desain ini didukung juga oleh pemrograman arsitektur yang dapat memberdayakan kembali sehingga narapidana perempuan menjadi produktif ketika berada di dalam penjara. Prototipe ini dapat memberikan sebuah keseimbangan ruang hidup kondusif yang dapat membantu mendorong narapidana perempuan dalam proses pemulihan atau rehabilitasi untuk integrasi kembali ke lingkungan masyarakat.